Implementasi Over Load Shedding (OLS) Pada Interbus Transformator (IBT) #3 31.5 Mva Dan IBT #5 31.5 MVA Di GI Tello 150/66 kV Untuk Menjaga Keandalan Suplai Ke GI Borongloe, GI Daya Dan GI Mandai - Thaha, Sarma; Adiyanti, Annisya; Usman, Usman; Sultan, Ahmad Rizal (Jurusan Teknik Elektro Politeknik Negeri Ujung Pandang, 2022)
Interbus transformer (IBT) is transformer that transfer power in different voltage level. Tello Substation has two IBT that change voltage level from 150 kV to 66 kV.Â In order to maintain the reliability operation of Tello substation, both IBT must be not allowed to overload. Overload condition could occur if one of the transformers is fault, the normal transformer will be overload.Â If an overload condition occurs, the two IBTs may not operate simultaneously. Due to this condition, it is necessary to prevent the occurrence of overload condition by applying overload shedding (OLS). This OLS application can prevent overload on the transformer if one of the transformers out of service due to fault condition. The OLS relay will work when the load on the IBT has reached its setting, by releasing the load on the 66 kV system line according to the OLS scheme as a precautionary step before all transformers trip. This research uses a case study on the Makassar Subsystem, which is one of the Sulbagsel System's electrical systems. The results showed that the amount of load that needed to be removed when implementing the OLS scheme at IBT #3 and IBT #5 31.5 MVA GI Tello was 16.86 MW. The OLS and OCR schemes are coordinated with the OLS setting current at each IBT GI Tello is 302.5 A, while the setting current for OCR at each IBT GI Tello is 330 andÂ time multiple setting ( tms) is 1.96